Toxicity mechanism of peri-implantation pesticide beta-cypermethrin exposure on endometrial remodeling in early pregnant mice. (1st May 2023) - Zhou, Yong-Jiang; Qiao, Qian-Feng; Wang, Li-Qing; Sheng, Tao-Yu; Cui, Man-Xue; Chen, Qi-Duo; Wang, Can-Yang; Zhang, Yun-Xiao
Abstract: Beta-cypermethrin (β-CYP) is a universally used pyrethroid pesticide with adverse effects on human health. β-CYP may impair endometrial remodeling in mice; however, the mechanism remains largely unknown. Endometrial remodeling plays a vital role in embryonic development and the maintenance of pregnancy. Therefore, we explored the mechanism by which peri-implantation β-CYP administration reduces uterine remodeling in pregnant mice. The C57BL/6 J pregnant mice were administered a dose of 20 mg/kg.bw. d β-CYP via oral gavage once daily from day 1 of gestation (GD1) to GD7. Molecular markers of endometrial remodeling, stromal cell proliferation, cell cycle regulation, and the PI3K/Akt/mTOR signaling pathway were evaluated in the decidual tissue of the uterus on GD7. An in vivo pseudopregnancy mouse model, a pregnant mouse model treated with an mTOR activator and an mTOR inhibitor and an in vitro decidualization model of mouse endometrial stromal cells were used to confirm β-CYP-induced defective endometrial remodeling and the key molecules expression of PI3K/Akt/mTOR signaling pathway. The results showed that β-CYP decreased the expression of the endometrial remodeling markers MMP9 and LIF in the uterine decidua. Peri-implantation β-CYP treatment markedly downregulated the expression of endometrial proliferation markers PCNA and Ki67 and decreased decidua thickness. Correspondingly, peri-implantation β-CYP exposure upregulated the expression of FOXO1, P57 and p-4E-BP1 in the decidua. Further experiments showed β-CYP significantly inhibited key molecules in the PI3K/Akt/mTOR pathway: PI3K, p-Akt/Akt, p-mTOR, and p-P70S6K in the uterine decidua. Additional experiments showed that aberrant endometrial remodeling induced by β-CYP was aggravated by rapamycin (an mTOR inhibitor) and partially reversed by MHY1485 (an mTOR agonist). In summary, our results indicated that a reduction in the PI3K/Akt/mTOR pathway may enhance defective endometrial remodeling by downregulating the proliferation and differentiation of endometrial stromal cells in early pregnant mice exposed to β-CYP. Our study elucidates the mechanism of defective endometrial remodeling induced by peri-implantation β-CYP exposure. Graphical Abstract: ga1